Accessibility manager: Creating a profile of a new profession - Zhang, Xiaochun (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2020)
Disability is viewed as part of the human condition. Measures aimed at promoting accessibility ensure that individuals with a disability can participate fully in society and on an equal footing with those who do not have a disability. Accessibility has been prioritized through regulations both nationally and globally. The Accessible Culture and Training project was funded by the ERASMUS + Programme of the European Union;[i]it promoted equal opportunities and access to cultural events across countries and languages. One of the main objectives of the project was to design a new job role entitled Accessibility Manager and to provide training associated with the position. This article reports on some of the intellectual outputs from the project, explains the process of defining the new job profile and discusses the skill set that has been identified. It concludes that the Accessible Culture and Training project responds appropriately to the formation of the new discipline, Accessibility Studies. [i] The Accessible Culture and Training project was funded by the ERASMUS + Programme of the European Union under the call Knowledge Alliance 2 with the reference 2015-1-ES01-KA203-015734.